2015
DOI: 10.1128/aem.00688-15
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Control over Dissimilatory Nitrate/Nitrite Reduction Pathways in Shewanella loihica Strain PV-4

Abstract: ؊ as a relevant modulator of NO 3 ؊ fate in S. loihica strain PV-4, and, by extension, suggest that NO 2 ؊ is a relevant determinant for N retention (i.e., ammonification) versus N loss and greenhouse gas emission (i.e., denitrification). T wo major dissimilatory pathways determine the fate of nitrate (NO 3Ϫ ) in anoxic environments: denitrification and respiratory ammonification (1, 2). In denitrification, NO 3 Ϫ is stepwise reduced via nitrite (NO 2 Ϫ ), nitric oxide (NO), and nitrous oxide (N 2 O) to dinitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…The measurements were adjusted for the weight of the salts in the culture medium that stayed on the membrane filter after filtration. This adjustment was necessary because media with different ionic strengths were used for the cultivation of the microorganisms (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were adjusted for the weight of the salts in the culture medium that stayed on the membrane filter after filtration. This adjustment was necessary because media with different ionic strengths were used for the cultivation of the microorganisms (30).…”
Section: Methodsmentioning
confidence: 99%
“…A Henry's constant of 2.21 was used to correct for the ionic strength effects in the saline medium used for culturing S. loihica (28)(29)(30). OD 600 measurements were performed with a Spectronic 20Dϩ spectrophotometer (Thermo Scientific, Waltham, MA) using disposable plastic cuvettes with a 1-cm path length.…”
Section: Methodsmentioning
confidence: 99%
“…However, comparison of lake parameters to DEA results (phenotype) and qPCR on N cycling genes (genotype) confirmed the lack of influence of nutrient inflow on the microbial community. It is possible the spatial distribution of microorganisms is not controlled by the amount of either organic carbon or nitrogen alone, but by their ratio in the sediments (Dang et al, 2009; Yoon et al, 2015a,b). Correlations also suggest that DEA results are unlikely to be influenced by any measured physical factors.…”
Section: Discussionmentioning
confidence: 99%
“…coli , differential expression of nrfA and nirB under low and high nitrate concentrations respectively was observed (Wang and Gunsalus, 2000 ). DNRA-related ecophysiology, enzymology, gene expression and regulation have been extensively studied in model organisms like E. coli, W. succinogenes , and B. subtilis (Cole, 1996 ; Nakano and Zuber, 1998 ; Simon, 2002 ), and more recently also in B. vireti (Mania et al, 2014 ) and Shewanella loihica (Yoon et al, 2015a , b ). Whole genome sequence analyses, however, demonstrated that DNRA, similar to denitrification, is phylogenetically very widespread, and can be found in members of Bacteroidetes (Mohan et al, 2004 ), Proteobacteria ( Gamma -, Delta -, and Epsilon ; Smith et al, 2007 ), Actinobacteria, Firmicutes, Acidobacteria, Chloroflexi , and Planctomycetes (Welsh et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some DNRA bacteria have furthermore been shown to contain partial or complete suites of genes for both DNRA and denitrification in their genome (Heylen and Keltjens, 2012 ; Sanford et al, 2012 ; Yoon et al, 2013 ; Mania et al, 2014 ). Functional capacity to carry out both nitrate reducing processes and the environmental drivers of nitrate partitioning to either process, like carbon-to-nitrogen ratios and nitrite concentrations, have thus far only been demonstrated for the marine strain Shewanella loihica PV-4 (Yoon et al, 2015a , b ). In addition to pure culture experiments, natural prokaryotic communities have also been used for examining these environmental drivers (Kraft et al, 2014 ; Van Den Berg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%